LAW ENFORCEMENT AGAINST DEFORESTATION IN THE RAWA SINGKIL WILDLIFE RESERVE - Luthfia, Rifda Arifa; Safrina; Listriani, Sophia (Zhata Institut, 2025)
Deforestation in the Rawa Singkil Wildlife Reserve continues to intensify despite its formal legal protection. This research aims to analyze the existing forms of legal protection governing the Rawa Singkil Wildlife Reserve and to examine the major obstacles hindering the implementation of environmental laws against deforestation. This Research using a normative juridical method with juridical, conceptual and statutory approaches. Data were obtained through extensive literature review and analyzed qualitatively using descriptive analysis. The study show that strengthening environmental governance has become increasingly urgent. Legal reforms such as Law Number 32 of 2024 amending Law Number 5 of 1990 are found to be inadequately enforced. Although the national legal framework provides administrative and criminal sanctions, overlapping authority, weak inter-agency coordination, limited supervision, and corruption in permit processes significantly undermine enforcement. Strengthening preventive legal mechanisms should be promoted through clearer boundary demarcation, improved community based environmental education, and stricter, digitally monitored licensing supervision. In addition, it is essential to ensure effective law enforcement and sustainable governance of the Rawa Singkil Wildlife Reserve.